Piptadenia gonoacantha-based natural dermocosmetic: a clinical trial - Paiva, Luciano Côrtes; Silva, Karen Vieira da; Almeida, Gabriel Feu Guarçoni de; Caldeira, Eliana Amaro de Carvalho; Cruz, Carlos Eduardo Soares Gazzinelli; Salgado, Patrícia de Oliveira; Amaro, Marilane de Oliveira Fani; Carvalho, Camilo Amaro de (Ciência e Natura, 2022)
The use of phytotherapy expands the possibility of therapeutic resources for the population, often offering reduced costs when compared to the pharmaceutical industry. In this perspective, the JACBIO® dermocosmetic ointment revealed, in non-clinical trials, its antibacterial and healing potential, with a great stimulating effect in increasing the production of images. This work aimed to carry out the clinical phase study on dermal toxicity, in serious humans, by applying JACBIO®, based on extracts from the leaves of Piptadenia gonoacantha (Pau Jacaré). The phase I randomized clinical trial was carried out with 28 clinically healthy patients at a public university in Minas Gerais, with no period from August to December 2018. The toxicological trial was developed with the intervention group that received a JACBIO® dermatological ointment and the Placebo group. From the experimental protocol, participants were followed for four weeks. An analysis between the ointment and placebo groups, without reference to anticholinergic and cardiovascular events, showed no statistically significant difference. Likewise, there was no difference in laboratory results performed before and after treatment, both for the placebo group and for the intervention group. A low toxicity of the product indicates that this adjustment is safe and serves as a basis for phase II clinical trials in patients with lesions.